Manajemen Keuangan SMA Negeri 3 Banjar Berdasarkan pada Analisis SWOT - Dian, Sri; Maryati, Erna; Syarifah, Syarifah (Journal of Management Review, 2024)
Financial management is the management of financial functions. Financial management involves part of planning, analysis (implementation), and financial control. Sudana (2017) suggests that the main obstacle in developing education is not solely on the financial aspect, but relies on the management aspect. Therefore, a SWOT analysis is needed to improve education and carry out effective financial management. In management there is strategic management so that schools can survive and improve their quality. In terms of management strategy, the most basic is analysis from various perspectives, both internal and external, which we usually know as SWOT analysis (strengths, weaknesses, opportunities, threats). The purpose of this study was to determine the financial management of SMA Negeri 3 Banjar based on a SWOT analysis. The method used in this study is a qualitative description. The research was conducted in Banjar City, which is located in SMA Negeri 3 Banjar. The results show that, at SMA Negeri 3 Banjar, the work program is always prepared based on a SWOT analysis and context analysis by identifying the 8 National Education Standards, so that double accounting does not occur in managerial implementation, especially in managing school institution finances because it has considered the weaknesses and strengths which will happen.